Assessment of Biological Soil Amendments of Animal Origin Use, Research Needs, and Extension Opportunities in Organic Production - Ramos, Thais Melo; Jay-Russell, Michele T.; Millner, Patricia D.; Shade, Jessica; Misiewicz, Tracy; Sorge, Ulrike S.; Hutchinson, Mark; Lilley, Jason; Pires, Alda F. A. (Frontiers in Sustainable Food Systems, 2019)
The use of biological soil amendments of animal origin (BSAAOs) to improve soil fertility and quality plays an important role in organic agriculture in the U.S. However, organic practices, such as untreated manure application, may introduce foodborne pathogens and consequently increase the risk of fresh produce contamination. Certified organic farms follow the USDA-National Organic Program (NOP) standards, which stipulate a 90- or 120-day waiting period between incorporating raw manure into the soil and crop harvest, depending on whether the edible portions of the crops come into indirect or direct contact, respectively, with the soil. To determine knowledge, attitudes, behaviors, and practices of organic farmers related to use of biological soil amendments, we employed three evaluation tools: a national workshop held at the University of California-Davis (UC-Davis); multiple in-person focus groups (listening sessions) conducted around the United States, and an online survey. Results reveal that untreated BSAAOs (untreated manure and immature composted manure) are critical tools in organic production for managing soil fertility and improving soil quality. Overall, organic producers surveyed in this study agreed that there is a need for more science-based data to evaluate and establish an appropriately protective time interval between untreated manure application and crop harvest to reduce the risk of surviving foodborne pathogens contaminating organic fresh produce. This study highlights the need for development of outreach and educational tools intended to help organic producers implement mitigation strategies to reduce food safety risks related to BSAAOs in organically grown produce covered by the Produce Safety Rule (PSR) of the U.S. Food and Drug Administration Food Safety Modernization Act (FSMA). This study informs and will aid prioritization of research (e.g., on a time interval protective of fresh produce food safety when soil is amended with animal-biological amendments in organic fresh produce systems) and outreach programs (e.g., GAPs, food safety programs, soil testing, pre-harvest food safety mitigation strategies, and organic rules and regulations) aimed at improving food safety for organic vegetable, fruit, and nut growers who use animal-based soil inputs, including amendments and rotational grazing.